Role of primary prophylaxis in preventing variceal bleeding in children with gastroesophageal varices - Way Seah Lee; Zhi Liang Song; Jun Min Em; Kee Seang Chew; Ruey Terng Ng (Elsevier, 2021)
Background: Primary endoscopic prophylaxis in pediatric gastroesophageal varices is not universally practiced. We aimed to determine the role of primary endoscopic prophylaxis in preventing variceal bleeding in gastroesophageal varices in children. Methods: We reviewed all children with gastroesophageal varices seen in our unit from 2000 to 2019. Primary prophylaxis was defined as endoscopic procedure without a preceding spontaneous bleeding and secondary prophylaxis as preceded by spontaneous bleeding. High-risk varices were defined as presence of grade III esophageal varices, cardia gastric varices or cherry red spots on the varices. Outcome measures (spontaneous rebleeding within 3 months after endoscopic procedure, number of additional procedures to eradicate varices, liver transplant [LT], death) were ascertained. Results: Sixteen of 62 (26%) patients (median [± S.D.] age at diagnosis = 5.0 ± 4.3 years) with varices had primary prophylaxis, 38 (61%) had secondary prophylaxis while 8 (13%) had no prophylaxis. No difference in the proportion of patients with high-risk varices was observed between primary (88%) and secondary (92%; P = 0.62) prophylaxis. As compared to secondary prophylaxis, children who had primary prophylaxis were significantly less likely to have spontaneous rebleeding (6% vs. 38%; P = 0.022) and needed significantly fewer repeated endoscopic procedures (0.9 ± 1.0 vs. 3.1 ± 2.5; P = 0.021). After 8.9 ± 5.5 years of follow-up, overall survival was 85%; survival with native liver was 73%. No statistical difference was observed in the eventual outcome (alive with native liver) between primary and secondary (71% vs. 78%, P = 0.78). Conclusion: Children with PHT who had primary prophylaxis had less subsequent spontaneous rebleeding and needed fewer additional endoscopic procedures as compared to secondary prophylaxis but did not have an improved eventual outcome. Screening endoscopy in all children who have signs of PHT and primary prophylaxis in high-risk esophageal varices should be considered before eventual LT.